ANALYSIS OF STUDENTS' SKILLS TO COMPLETE SCHOOL EXAMS BASED ON THE MINIMUM COMPETENCY ASSESSMENT - Andri Rahadyan; Indra Kurniawan (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2022)
This study analyses students' skills to complete school exam questions based on the minimum competency assessment (MCA). This study employs qualitative and descriptive methods to characterize students' MCA-based School Examination question-solving abilities. The subjects of this study were class XII students at HSPG Bekasi who completed MCA-based school exams containing literacy and numeracy skills. In addition to collecting samples by interviewing six students, the researchers gathered data to describe students' abilities. Students answered a total of forty questions. This study found four students with low numeracy skills, 13 with moderate skills, and three with high skills. Low, medium, and increased literacy levels were determined through interviews. Students with weak literacy skills struggle to read algebra or geometry questions, indicating they have soft numeracy skills. Medium-literacy students like the story and simple context questions. They cannot answer questions because they cannot remember formulas. High-literacy students. They like story questions and questions with real-world contexts because they let us apply our skills and understand existing procedures. They struggle with knowledge-based questions. Because additional reasoning takes so much time, students with high literacy have average numeracy skills. So, the students' problem-solving skills improve.